Geraniol Encapsulated in Chitosan/Gum Arabic Nanoparticles: A Promising System for Pest Management in Sustainable Agriculture - De Oliveira, Jhones Luiz [UNESP]; Campos, Estefânia Vangelie Ramos; Pereira, Anderson E. S.; Nunes, Lucas E. S. [UNESP]; Da Silva, Camila C. L. [UNESP]; Pasquoto, Tatiane; Lima, Renata; Smaniotto, Giovani [UNESP]; Polanczyk, Ricardo Antonio [UNESP]; Fraceto, Leonardo F. [UNESP] (American Chemical Society (ACS), 2018)
The nanoencapsulation of botanical compounds (such as geraniol) is an important strategy that can be used to increase the stability and efficiency of these substances in integrated pest management. In this study, chitosan/gum arabic nanoparticles containing geraniol were prepared and characterized. In addition, evaluation was made of the biological activity of geraniol encapsulated in chitosan/gum arabic nanoparticles toward whitefly (Bemisia tabaci). The optimized formulation showed a high encapsulation efficiency (>90%) and remained stable for about 120 days. The formulation protected the geraniol against degradation by UV radiation, and the in vitro release was according to a diffusion mechanism that was influenced by temperature. An attraction effect was observed for Bemisia tabaci, indicating the potential of this type of system for use in pest management, especially in trap devices.
Keywords: botanical active agent; environmentally friendly; toxicity